Marino Faliero by Eugene Delacroix — a Venetian Picture - Sedleryonok, Valeria D. (Actual Problems of Theory and History of Art, 2018)
Marino Faliero by Eugene Delacroix is one of the key paintings of the 19th century which has not been sufficiently researched. Created in the middle of the 1820s and exhibited in French Salon of 1827 for demanding Parisian public, this canvas became one of the indicators of the artistic changes, which new decade brought. The present research is the first versatile analysis of the painting, based primarily on the detailed investigation of the historical sources, both verbal and visual, of the 19th century Parisian and Venetian artworks, museum catalogues, art reviews, and newspapers. Among them there are works of Eugene Delacroix, and his contemporaries, paintings of Venetian artists of the 16th century, notes in the Paris press of the 1820s, such editions, as Le Constitutionnel, Journal des débats, Journal des artistes, Le Figaro, L’Observateur, Le Globe, Revue de Paris, and La Pandore. The purpose of the article is not only to analyze the characteristics and the perception of Marino Faliero, to define its place and role in the artistic, social, and political context of 1820s Paris, but also to address a wider range of questions linked to the painting with regard to forming a new artistic language in France. All the above reveals the significance of Delacroix’s Venetian painting for understanding the patterns of art development in the 19th century.